7(n-6)=-6(-n+6)

Simple and best practice solution for 7(n-6)=-6(-n+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(n-6)=-6(-n+6) equation:


Simplifying
7(n + -6) = -6(-1n + 6)

Reorder the terms:
7(-6 + n) = -6(-1n + 6)
(-6 * 7 + n * 7) = -6(-1n + 6)
(-42 + 7n) = -6(-1n + 6)

Reorder the terms:
-42 + 7n = -6(6 + -1n)
-42 + 7n = (6 * -6 + -1n * -6)
-42 + 7n = (-36 + 6n)

Solving
-42 + 7n = -36 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-42 + 7n + -6n = -36 + 6n + -6n

Combine like terms: 7n + -6n = 1n
-42 + 1n = -36 + 6n + -6n

Combine like terms: 6n + -6n = 0
-42 + 1n = -36 + 0
-42 + 1n = -36

Add '42' to each side of the equation.
-42 + 42 + 1n = -36 + 42

Combine like terms: -42 + 42 = 0
0 + 1n = -36 + 42
1n = -36 + 42

Combine like terms: -36 + 42 = 6
1n = 6

Divide each side by '1'.
n = 6

Simplifying
n = 6

See similar equations:

| 3(x+4)=-3(x+8) | | -80=8(-4-6m) | | 6y+2x=180 | | -6+3x=-3x+24 | | 3n+10-4n-11= | | x^2+512=0 | | 6=-6(n-8) | | 9a+4-2a=53 | | x^3+x^2+2x-4=0 | | 3(3x+7)+4(5x-2)= | | -1.5h+6.5h=50 | | 2(4k-6)= | | 8a-16=4a+12 | | 3.44-1.25x=1.05(2.38x+681) | | 17=3(p-5)8 | | 21=7(-3+6) | | 2y+4x=3 | | 4x^3+10x^2+5x+2=0 | | 25y-6y=76 | | 2x+4=3(x-7) | | M-200=100 | | 3y-10x=67 | | 55m-4=-6(m+2) | | .8b+1.9=5.5-.4b | | 5(-2+2)=3(-4+6) | | 10=6x-2x-8 | | -35=x-18 | | .8b+1.9=5.5-4b | | 2x+x+30=90 | | -35=x+18 | | 4x+4=-20-2x | | 3/5--2/5= |

Equations solver categories